Measurement of associated production of z bosons with charm quark jets in pp collisions at √s=1.96 TeV - Abazov, V M; Abbott, B; Acharya, B S; Adams, M; Adams, T; Agnew, J P; Alexeev, G D; Alkhazov, G; Alton, A; Askew, A; Atkins, S; Augsten, K; et al. (Physical review letters, 2014)
We present the first measurements of the ratios of cross sections σ(pp → Z+c jet)/σ(pp → Z+jet) and σ(pp → Z+c jet)/σ(pp → Z+b jet) for the associated production of a Z boson with at least one charm or bottom quark jet. Jets have transverse momentum ​pT(jet)​>20 GeV and pseudorapidity |​η(jet)​|<2.5. These cross section ratios are measured differentially as a function of jet and Z boson transverse momenta, based on 9.7 fb(-1) of pp collisions collected with the D0 detector at the Fermilab Tevatron Collider at √s=1.96 TeV. The measurements show significant deviations from perturbative QCD calculations and predictions from various event generators.